2020
DOI: 10.1097/md.0000000000022908
|View full text |Cite
|
Sign up to set email alerts
|

Association between PLA2R1 rs4664308 and susceptibility to idiopathic membranous nephropathy

Abstract: Previous studies have evaluated the association between the phospholipase A2 m-type receptor ( PLA2R1) rs4664308 polymorphism and the risk of idiopathic membranous nephropathy (IMN), but the results need to be integrated. We hypothesized that the PLA2R1 rs4664308 polymorphism is associated with IMN risk in different ethnicities and assessed this hypothesis by using meta-analysis and case-control studies. A literature searches on PLA2R1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In fact, over the past decade several studies focused on PLA2R and HLA-DQA1 gene polymorphisms, though with inconsistent findings. Although, previous meta-analyses were published in 2018 for the HLA-DQA1 rs2187668 SNP, 8 and in 2020 for the PLA2R rs4664308 SNP, 6 , 7 the literature search cut-off time in our study was fresher. Besides, to the best of our knowledge, this study was the first to summarize published results on PMN risk conferred by the following PLA2R SNPs, rs3749117, rs3749119, rs35771982, rs3828323, rs16844715, rs1511223, rs6757188, and rs2715918.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In fact, over the past decade several studies focused on PLA2R and HLA-DQA1 gene polymorphisms, though with inconsistent findings. Although, previous meta-analyses were published in 2018 for the HLA-DQA1 rs2187668 SNP, 8 and in 2020 for the PLA2R rs4664308 SNP, 6 , 7 the literature search cut-off time in our study was fresher. Besides, to the best of our knowledge, this study was the first to summarize published results on PMN risk conferred by the following PLA2R SNPs, rs3749117, rs3749119, rs35771982, rs3828323, rs16844715, rs1511223, rs6757188, and rs2715918.…”
Section: Discussionmentioning
confidence: 90%
“…Three previous meta-analyses assessing PMN genetic risk; 2 for the PLA2R rs4664308 polymorphism (SNP) in 2020 6 , 7 ; and 1 for the HLA-DQA1 rs2187668 SNP in 2018 8 ; have been already published. Nevertheless, these aforementioned meta-analyses included only a few studies (7–11) and revealed a high level of between-study heterogeneity with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations